من منظور الشريعة الإسلامية: دراسة فقهية تحليلية (BNPL) تقييم خدمات اشتر الآن وادفع لاحقًا : Evaluation of Buy Now, Pay Later (BNPL) Services from Islamic Sharia Perspective: An Analytical Jurisprudence Study - al Obaid, Alaa (Jurnal Fiqh, 2024)
This research explores the growing popularity of Buy Now, Pay Later (BNPL) services and their alignment with Islamic Sharia principles. As these services gain traction among Muslims, it is essential to ensure compliance with Sharia laws in financial transactions. The study highlights the necessity to evaluate BNPL’s adherence to rules regarding riba (interest), gharar (uncertainty), and fairness, aiming to clarify their permissibility under Islamic jurisprudence. The research employs an analytical jurisprudential approach, reviewing Sharia sources, fatwas, and interviews with scholars. Key findings suggest that while some BNPL contracts conflict with Sharia due to interest charges and fees, they can be adapted to comply by removing these elements and promoting transparency. The study underscores the importance of educating companies and consumers on Sharia-compliant models and consulting scholars to develop alternative financing solutions that align with Islamic values.